Advances in protease inhibition-based chemotherapy: A decade of insights from Malaria research - Sojka, Daniel; Šnebergerová, Pavla (Advances in parasitology, 2024)
Over the last decade, research on the most studied parasite, Plasmodium falciparum, has disclosed significant findings in protease research. Detailed descriptions of the individual roles of protease isoenzymes from various protease classes encoded by the parasite genome have been elucidated, along with their functional and biochemical characterizations. These insights have enabled the development of innovative chemotherapy using low molecular weight inhibitors targeting specific molecular sites. Progress has been made in understanding the proteolytic cascade associated with the apical complex, particularly the roles of aspartyl proteases plasmepsins IX and X as master regulators. Additionally, advancements in direct and alternative methods of proteasome inhibition and expression regulation have been achieved. Research on digestive/food vacuole-associated proteases, with a focus on essential metalloproteases, has also seen significant developments. The rise of extensive genomic datasets and functional genomic tools for other parasitic organisms now allows these approaches to be applied to the study and treatment of other, less known parasitic diseases, aiming to uncover specific biological mechanisms and develop innovative, less toxic chemotherapies.
Keywords: tropická malárie; malárie; Malaria; Animals; antimalarika; Plasmodium falciparum; Humans; lidé; Protease Inhibitors; proteasy; inhibitory proteas; Antimalarials; zvířata; Malaria, Falciparum; Peptide Hydrolases